Transfusion related acute lung injury-TRALI: a review - Alcazar-Castro, Javier; Zarate-Aspiros, Alejandro; Andrade-Cuellar, Elias; Alvarez-Perez, Brenda; Valderrama-Treviño, Alan I.; Granados-Romero, Juan J.; Banegas-Ruiz, Rodrigo; Barrera-Mera, Baltazar; Alvarado-Rodriguez, Cristopher; Uriarte-Ruiz, Karen (International Journal of Research in Medical Sciences, 2019)
Acute pulmonary damage caused by transfusion is characterized by the sudden onset of respiratory distress in newly transfused patients within 6 hours after the transfusion, bilateral infiltrative changes in chest X-ray, PaO2/FIO2 <300 mmHg, absence of other risk factors for acute lung injury and absence of signs suggesting cardiogenic origin of pulmonary edema. Being one of the most serious complications of blood transfusion, plasma is the most involved factor, although all blood components can cause it, and is caused by antigen reactions/leukocyte antibody and lipid activity with ability to modify the biological response on primitive leukocytes. The diagnosis is based on the integration of clinical, radiological and gasometric elements, ruling out the rest of the possible causes of acute lung injury. Its differential diagnosis should include hemodynamic overload, anaphylactic reaction, bacterial contamination of transfused blood products and transfusion hemolytic reaction. The treatment is supportive measures based on the needs and does not differ from the treatment of acute lung injury secondary to other etiologies, severe cases require endotracheal intubation and mechanical ventilation while the non-severe can be managed with oxygen therapy.